The importance of thermodynamics for molecular systems, and the importance of molecular systems for thermodynamics - Ouldridge,TE (Natural Computing, 2017)
Improved understanding of molecular systems has only emphasised thesophistication of networks within the cell. Simultaneously, the advance ofnucleic acid nanotechnology, a platform within which reactions can beexquisitely controlled, has made the development of artificial architecturesand devices possible. Vital to this progress has been a solid foundation in thethermodynamics of molecular systems. In this pedagogical review andperspective, I will discuss how thermodynamics determines both the overallpotential of molecular networks, and the minute details of design. I will thenargue that, in turn, the need to understand molecular systems is helping todrive the development of theories of thermodynamics at the microscopic scale.